2018
DOI: 10.3892/mmr.2018.9387
|View full text |Cite
|
Sign up to set email alerts
|

Identification of LINC01279 as a cell cycle‑associated long non‑coding RNA in endometriosis with GBA analysis

Abstract: Endometriosis affects 6–10% of women of reproductive age. Though a significant amount of research has explored the pathogenesis of endometriosis, little is clear. Elucidating the mechanisms is urgently required for improving the therapeutic efficiency of endometriosis treatment. Long non-coding RNAs (lncRNAs) have recently acquired extensive attention as regulatory components in a variety of biological processes and diseases. However, the functions of many lncRNAs in endometriosis are poorly understood. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Based on Liu et al study, there is a strong association between this lncRNA and cell cycle-dependent kinase-14 and CXC motif chemokine ligand-12. Hence, LINC01279 might contribute in the pathogenesis of endometriosis 54 . In another bioinformatics analysis of differential gene expression in breast cancer LINC01279 was significantly down-regulated 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on Liu et al study, there is a strong association between this lncRNA and cell cycle-dependent kinase-14 and CXC motif chemokine ligand-12. Hence, LINC01279 might contribute in the pathogenesis of endometriosis 54 . In another bioinformatics analysis of differential gene expression in breast cancer LINC01279 was significantly down-regulated 55 .…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA‐LINC01279 is a class of lncRNA molecules. Recently, some scholars have found the increased expression of lncRNA‐LINC01279 in EMs through guilt‐by‐association analysis and confirmed the correlation between lncRNA‐LINC01279 and EMs 20 …”
Section: Discussionmentioning
confidence: 92%
“…In recent research, researchers found that HOXA10 expression was significantly lower in EMs patients than in healthy subjects, and the expression level of endometrial HOXA10 gene was also significantly lower in infertile EMs patients than in fertile EMs patients 18,19 . It has been confirmed that LncRNA‐LINC01279 is upregulated in EMs and plays an important role in regulating the cell cycle and in working with other key regulators in EMs, including cyclin‐dependent kinases and CXCR12 20 …”
Section: Introductionmentioning
confidence: 93%
“…They are the most common noncoding RNAs and are involved in cell proliferation, differentiation, and apoptosis; all processes central in the pathobiology of endometriosis [21]. Some lnc-RNAs proposed as diagnostic markers of endometriosis include: H19 [22], CHL1-AS2 microRNA and Overcoming the Challenges of Their Use in the Diagnosis of Endometriosis DOI: http://dx.doi.org/10.5772/intechopen.91324 [23,24], AC002454.1 [25], lncRNA SRA (steroid receptor RNA activator) [26], MALAT-1 [27], and LINC01279 [28]. Results of a recent study revealed the lnc-RNA are carried in circulating extracellular vesicles in women with endometriosis [29].…”
Section: Candidate Clinical Markers Of Endometriosismentioning
confidence: 99%